The Turn to Gramsci in Critical Studies in Education in North America - Mayo, Peter (International Gramsci Journal, 2023)
This article explores the impact of Gramsci’s writings (in particular pedagogy as a hegemonic relation) on Critical Studies in Education (CSE) in North America. CSE focuses among other things on education for social justice and ecological questions. It refuses the separation of culture from power relations, and attempts to reconstruct knowledge to serve social needs through its insertion in the interstices of social reproduction, schools included. Indeed the classroom is one site for a war of position. But the school – and the university – are not the only institutions of and for education, which takes place as a lifelong process during which subaltern groups can use their critical learning capacities within and outside dominant class-based forms of knowledge. This locates the intellectuals produced by the subaltern groups in a two-way relationship with teachers, considered in their position as organic and potentially transformative intellectuals: in short there is a pedagogical relation that characterizes every form of hegemony and which here can form part of an alternative hegemony to that of the dominant classes. And in establishing an alternative hegemony, taking Freire and Gramsci each in their own way as reference points, one has to move from popular experience to then go on to movements or parties and the wider social context.